Successful Management of Cervical Ectopic Pregnancy in a Primigravida with Dilation and Evacuation: A Case Report - Dr. Avishek Bhadra; Dr. Rumela Biswas; Dr. Anubhuti Jha; Dr. Subhojit Bagchi, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Cervical ectopic pregnancy (CEP) is a rare and potentially life-threatening condition, particularly in primigravid patients. This case presents a 20-year-old primigravida with painless vaginal bleeding at 8 weeks of amenorrhea, diagnosed with CEP via early pregnancy ultrasound. The patient underwent a successful emergency dilation and evacuation (D&E) procedure, preserving fertility and preventing excessive hemorrhage. Postoperative recovery was uneventful, and follow-up ultrasound confirmed complete evacuation. This case highlights the importance of early diagnosis and careful management of CEP, particularly in terms of preserving future fertility and minimizing complications like hemorrhage and cervical insufficiency.